Pathogenicity of Root- Knot Nematodes Meloidogyne incognita on Pongamia pinnata Tree Seedlings - Sivaprakash, M.; Balasubramanian, P.; Rathakrishnan, P. (Indian Journal of Agroforestry, 2020)
A polythene bag culture experiment was conducted in a glasshouse to assess the pathogenicity of root-knot nematode, Meloidogyne incognita on Pongamia pinnata. Bags (15 cm x 10 cm) were filled with steam sterilized fine river sand mixed with red earth at the ratio of 3: 1. The freshly collected, surface sterilized seeds were sown. Fifteen days after germination of seedlings, second stage larvae of M. incognita were inoculated in the root zone of P. pinnata at the rate of 0, 10, 100, 1000 and 10,000 larvae bag-1. Each treatment was replicated four times and arranged in a RBD in glass house at a temperature of 27 °C. The plant growth parameters, number of galls, rhizobial nodules, egg masses on root, larvae, adult females and final soil populations were recorded after 120 days after inoculation (DAI). The chlorophyll content and other physiological parameters were also recorded at 120 DAI. The results revealed progressive reduction in length and weight of shoot and root significantly with the increase in the level of initial inoculum. The percentage of reduction in shoot length, shoot weight, root length and root weight were 38.6, 41.4, 18.3 and 34.7, respectively to the initial inoculum of 10,000 larvae when compared to un inoculated control. It was found that at an initial inoculum level of 10,000 larvae kg-1 soil, the collar diameter got decreased by 26.3 per cent over control. Significant reduction of rhizobial nodule was recorded for every level of larvae inoculated on P. pinnata. The respective per cent reduction in nodule and its diameter registered was 45.9 and 22.2, 56.4 and 26.7 and 59.2 and 40.0 to 100, 1000 and 10,000 larvae kg-1 soil over uninoculated control respectively. There was significant reduction in chlorophyll 'a', chlorophyll 'b' and total chlorophyll in the inoculated plants. Stomatal conductance, transpiration and net photosynthetic rate in inoculated plant also showed significant decrease as compared to the uninoculated control.